التخطيط الإقليمي والاستثمار الأمثل للأراضي الزراعية في محافظة اللاذقية من الفترة 2003 – 2009 - العلي, إبراهيم; ناصر, فراس (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تطور المساحات المستثمرة وغير المستثمرةللأراضي في محافظة اللاذقية خلال الفترة 2002 – 2009 ، وكذلك دراسة الفروق بين المناطق حسب نسب الأراضي المستثمرة، والعلاقة بين المساحات المستثمرة وعدد السكان بين المناطق،وبين زيادة عدد السكان وحصة الفرد من المساحات المستثمرة في المحافظة، ولتحقيق أغراض البحث قام الباحث بدراسة تطور المؤشرات المتعلقة بذلك، نظراً لأهمية ذلك في عملية التنمية ، وانتهى البحث إلى أن هناك فروقاً في نسب الأراضي المستثمرة بين المناطق، وأن حصة الفرد من المساحات المستثمرة تتناقص بزيادة عدد السكان في منطقتي اللاذقية والحفة، وأيضاً هناك فروق في حصة الفرد من المساحات المستثمرة بين المناطق في المحافظة. This research aims to study developing of un-invested and invested lands in Lattakia Mohafaza within period 2002-2009, so study variances among district according land use, and relation among invested lands and population number, and among number of population and share of person of invested lands in Mohafaza, and for achieving that objects, researcher has been studied dynamic of indictors that related by, and the research reaches to that, there are statistical denotation variances among invested land rates according districts, and the share of person of invested lands decrease by increase number of population in Lattakia and AL-Haffa districts, and there are statistical denotation variance for share of person's invested lands among districts in Lattakia Mohafaza .